Habits, contingency, orality: Insights into the idea of “living literature” moving from Leopardi (Itinera, 2024)
What is the relationship between habit and literary creativity? What role does the notion of habit play in the process of composition and, in general, in artistic productivity and the aesthetic experience? How do the terms habit and improvisation, habituation and contingency relate to each other? To answer these questions, crucial for aesthetics, this essay moves from the discussion of some significant passages in Giacomo Leopardi’s Zibaldone. On the one hand, the notions of habit and habituation will be discussed, understood – in the specific case of their application to poetry – as the poetic work of giving oneself a form; on the other hand, I shall analyze the notion of environmental or contextual contingency as the input that activates the poetic composition, in terms of a so-called “deliberate improvisation”. Against the background of these interconnected concepts the issues of the relationship between book and orality, performativity and recitation, lowbrow culture and highbrow culture will emerge, in a dense web of cross-references that defines, at least in its general lines, one of the axes of Leopardi's theoretical thinking around the 1820s.
Keywords: Zibaldone, book, improvisation, environment.